Defying the Odds: A Case of Successfully Treated Harlequin Ichthyosis in Lebanon - Bassel Hamam; Sarah Saleh; Miled Yaacoub; Houssein Chebbo; Sarah Jalloul; Karam Karam; Rima Houmani (Clinical Case Reports)
ABSTRACT Harlequin ichthyosis is a rare skin disorder affecting newborns characterized by a scaly skin, flexed limbs, ectropium, and eclabium. The overall incidence of HI is 1 in 300,000 births, with approximately only 200 cases reported worldwide. Some studies uncovered a TH17 immune skewing in patients with HI, which is also seen in psoriasis. We herein present a case of a newborn found to have harlequin ichthyosis, whom his mother is known to have psoriasis. The baby was treated with topical antibiotics and retinoid creams. The baby then exhibited smoother skin with less scaling and flatter fissures.